Aircraft sustainment and repair - Jones, R.; Baker, A. A.; Matthews, Neil; Champagne, Victor K. (Butterworth-Heinemann, 2018)
Aircraft Sustainment and Repair is a one-stop-shop for practitioners and researchers in the field of aircraft sustainment, adhesively bonded aircraft joints, bonded composites repairs, and the application of cold spray to military and civil aircraft. Outlining the state-of-the-art in aircraft sustainment, this book covers the use of quantitative fractography to determine the in-service crack length versus flight hours curve, the effect of intergranular cracking on structural integrity and the structural significance of corrosion. The book additionally illustrates the potential of composite repairs and SPD applications to metallic airframes.
Keywords: Airplanes -- Maintenance and repair.; elektronické knihy; electronic books